2022
DOI: 10.1155/2022/9961513
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cytotoxic, Genotoxic, and Oxidative Stress of Dibutyl Phthalate on Cultured Bovine Peripheral Lymphocytes

Abstract: Recently, there have been numerous reports showing that phthalates have negative human health impacts and may cause several diseases such as asthma, breast cancer, obesity, type II diabetes, and male infertility. Animals are also exposed to phthalates through the environment and can cause adverse health effects on them. Several studies have been found on the cytogenetic effects of dibutyl phthalate (DBP) on different organisms but no documented evidence has been found on the cytotoxic and genotoxic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The results of this study suggested that the GBM group had higher tail intensity in the liver in the comet assay compared with the trained groups, and these results were reversed with physical training. Observations made using the comet test suggest that genomic injuries can lead to mutations [50][51][52]. Our results showed that the group that received GL261 cells and did not exercise had higher tail intensity in hepatocytes compared with the trained sham and GBM groups, indicating greater DNA damage, which has been previously observed in studies that associate comet assay and physical exercise.…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study suggested that the GBM group had higher tail intensity in the liver in the comet assay compared with the trained groups, and these results were reversed with physical training. Observations made using the comet test suggest that genomic injuries can lead to mutations [50][51][52]. Our results showed that the group that received GL261 cells and did not exercise had higher tail intensity in hepatocytes compared with the trained sham and GBM groups, indicating greater DNA damage, which has been previously observed in studies that associate comet assay and physical exercise.…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study suggested that the GBM group had higher tail intensity in the liver in the comet assay compared with the trained groups, and these results were reversed with physical training. Observations made using the comet test suggest that genomic injuries can lead to mutations [49][50][51]. Our results showed that the group that received GL261 cells and did not exercise had higher tail intensity in hepatocytes compared with the trained sham and GBM groups, indicating greater DNA damage, which has been previously observed in studies that associate comet assay and physical exercise.…”
Section: Discussionsupporting
confidence: 75%
“…Under normal physiological conditions, cells are capable of counterbalancing the noxious effects of ROS with the antioxidant defense system which consists of free radical scavengers such as SOD, GSH, glutathione peroxidase (GPx), and CAT. When production of free radicals exceeds the body's antioxidant defense system, it results in oxidative stress [42]. It is imposed on cells due to increase in oxidant generation, a decrease in antioxidant protection, and failure in the repair of oxidative damage [43][44][45][46] in the form of severe damage to cellular macromolecules such as proteins, lipids, and DNA, resulting in detrimental effects on cells [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%